Bezafibrate for the treatment of hypertriglyceridemia in HIV1-infected patients on highly active antiretroviral therapy - Geraix,Juliana (2006)
The use of highly active antiretroviral therapy (HAART) in HIV-infected patients has been associated with the development of risk factors for cardiovascular diseases (CD) including dyslipidemia and insulin resistance, hypertriglyceridemia being the most frequent metabolic disturbance in these patients. Fibrates are indicated when hypertriglyceridemia is accentuated and persists for over six months. We evaluated the efficacy and safety of bezafibrate for the treatment of hypertriglyceridemia in HIV-infected individuals on HAART. All patients received 400mg/day of bezafibrate and were evaluated three times: Mo (pre-treatment), M1 (one month after treatment), and M2 (six months after treatment). Fifteen adult individuals, eight males and seven females with mean age = 41.2 ± 7.97 years and triglyceride serum levels > 400mg/dL were included in the study. Smoking, alcohol ingestion and sedentarism rates were 50%, 6.66% and 60%, respectively. Family history of CD, hypertension and diabetes mellitus was reported in 33.3%, 40% and 46.7% of the cases, respectively, while dyslipidemia was reported by only 13.3%. More than half of the patients were using a protease inhibitor plus a nucleotide analog transcriptase inhibitor. Eutrophy and tendency toward overweight were observed at all three study time points. There were significant reductions in triglyceride serum levels from Mo to M1 and from Mo to M2. No significant changes were observed in the serum levels of creatine phosphokinase, hepatic enzymes, CD4+, CD8+ and viral load. Therefore, bezafibrate seems to be safe and effective for the reduction of hypertriglyceridemia in HIV-infected patients on HAART.